The Effect of Online Seminars on Public’s Knowledge About the Covid-19 Pandemic in the New Normal Era - Apriyani Supia Dewi; Nur Ghaliyah Sandra (Community Medicine and Education Journal, 2021)
Covid-19 (Coronavirus Disease 2019) is a disease transmitted between animals and humans (zoonosis) by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV2). A total of 70,736 confirmed cases of Covid-19 and 3,417 deaths have been reported by the Ministry of Health (9 July 2020). Various steps have been taken to control the spread of the Covid-19 pandemic that is currently happening in Indonesia, one of which is health promotion. During the Covid-19 pandemic, it was suggested that educational methods be better done online. So, this study is interested in assessing the effect of the educational method with online seminars through WhatsApps on the knowledge of the general public about covid-19 and the new normal policy. This study uses a research design quasi experimental pre and post test design by comparing the knowledge of respondents before and after observation. Observations were made when respondents attended online seminars about covid-19 and new normal via the WhatsApp group. The population in this study were 416 people who were members of the online seminar group conducted by the IKM-IKK FK Unsri department. In this study, 171 respondents met the inclusion and exclusion criteria. The results of the univariate analysis regarding the characteristics of the respondents obtained an average age 28.61 years, female (61.4%), and not yet working (45.6%), including students and college students. It was found that the level of knowledge of respondents about Covid-19 increased from 43.9% becomes 77.8%. Likewise, the respondents good knowledge about the new normal increased from 9.9% becomes 42.1%. On comparative analysis showed a significant change in knowledge about Covid-19 and new normal respondents after attending an online seminar, namely p= 0,000 and p= 0,000. So, it can be concluded that online seminars have a significant effect on changes in the knowledge of the general public about Covid-19 and the new normal.